Screen time, physical activity and self-esteem in children: the Ulm birth cohort study - Braig, Stefanie; Brenner, Hermann; Rothenbacher, Dietrich (International journal of environmental research and public health, 2018)
Screen time is a central activity of children's daily life and jeopardizes mental health. However, results appear inconclusive and are often based on small cross-sectional studies. We aimed to investigate the temporal sequence of the association between screen time and self-esteem taking into account further indirect effects through family or friendship relationship. In our population-based birth cohort study (baseline November 2000 - November 2001, Ulm, Germany), these relationships were explored in n = 519 11- and 13-year-old children and their parents who both provided information on children's screen time: time spent watching television or videos (TV), time spent on computers, video game consoles, mobile devices, or cell phones; so called "other screen time", and children's self-esteem (KINDL-R). Time watching TV (self-reported) at age 11 was negatively associated with girls' self-esteem at the same age but positively with an increase of self-esteem between age 11 and 13. However, the latter association was restricted to low to moderate TV viewers. In boys, a higher increase of other screen time between age 11 and age 13 was associated with lower self-reported self-esteem at age 13. Additionally, friendship relationship mediated the association between watching TV and self-esteem in girls. For parental reports similar associations were observed. These findings indicate that time sequence and potential mediators need further investigation in cohort studies with multiple assessments of screen time and self-esteem.